(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The use of electronic courts in India represents a noteworthy advancement in the modernization of the legal system, to augment accessibility, efficacy, and transparency. Electronic courts, or e-courts, use information and communication technology to expedite the legal process and offer online services to those involved, including advocates and litigants.The goal of the reform initiatives aimed at improving India's legal institutions is to decrease the number of cases in the court system and increase judicial efficiency. The Supreme Court's E-Committee's suggested reform laysfor a digital infrastructure that encourages transparency and interoperability. The first objective of the study is to focus on the development of e-courts in India. The study's second objective is to discuss the impact of e-courts on advocacy and other factors. And the third objective of the study is to analyse the challenges to accepting digitalization in the judiciary. The importance of the study is to develop the skill of digitalizing courts for budding lawyers and future judges.